2006
DOI: 10.1196/annals.1375.050
|View full text |Cite
|
Sign up to set email alerts
|

Protection From Type 1 Diabetes by Vitamin D Receptor Haplotypes

Abstract: Vitamin D has been involved in the modulation of calcium and bone metabolism as well as in the immune system, where it suppresses the proliferation of activated T cells. These effects are exerted via the vitamin D receptor (VDR). Polymorphisms within this gene have been exhaustively studied in diverse autoimmune diseases but with inconsistent results. We previously reported a positive association of polymorphisms within the VDR gene (Apa I, Taq I, Bsm I, and Fok I). In the present article we extended our previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 19 publications
0
38
1
3
Order By: Relevance
“…Certain allelic variants in VDR have been related to diabetes. In a German population, combinations of BsmI/ ApaI/TaqI influenced susceptibility to type 1 diabetes (T1D) [5]. In a Taiwanese population the AA genotype of ApaI polymorphism was associated with T1D.…”
Section: Introductionmentioning
confidence: 99%
“…Certain allelic variants in VDR have been related to diabetes. In a German population, combinations of BsmI/ ApaI/TaqI influenced susceptibility to type 1 diabetes (T1D) [5]. In a Taiwanese population the AA genotype of ApaI polymorphism was associated with T1D.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the vitamin D status is a priori not likely to signal male health, and it is therefore not terribly likely, although not totally excluded, that provitamin D plays a role as a pheromone in humans as well, but this observation in the amphibians illustrates that this substance still holds surprises and has a plethora of nonclassical actions, for example, in immune function (8), ␤ cell function (29,30), apoptosis (31), cell-cycle control (32), and control of renin secretion (33), to mention only a few. Deservedly, these nonclassical actions, called "pleiotropic" (literally "directed in diverse directions"), have recently attracted considerable interest in the renal community (34).…”
Section: Results Of the Readoutsmentioning
confidence: 99%
“…Recently, Ramos-Lopez et al investigated 11 polymorphisms, also including the same four polymorphisms from our study, in German families. They found several VDR gene haplotypes to be negatively associated with T1DM (Ramos-Lopez et al 2006). Mimbacas et al investigated three VDR SNPs and found FokI to be an indicator for susceptibility to T1DM in a Uruguayan population (Mimbacas et al 2007).…”
Section: Discussionmentioning
confidence: 99%